Kepemimpinan Pendidikan Dalam Kontek Islam - Suadi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
The existence of a leader in an educational institution is very important because it is one of the elements that will determine the preparation and process of realizing the institutional vision. Islamic, good and firm leadership is needed in every educational institution. because basically every educational institution needs a leader figure who masters various matters related to education. The success or failure of an educational institution is largely determined by the quality of leadership, because an outstanding school is a school that has effective leadership. This research includes library research, which is research that utilizes library sources to obtain research data, while the approach used is a qualitative research approach, namely systematic research used to study or research an object in a natural setting without any manipulation therein and without there is a hypothesis test. From this research, the concept of Islamic educational leadership is the art or skill of a leader influencing his subordinates in an effort to achieve educational goals in accordance with Islamic principles. The criteria for a leader who is the hope in Islamic education must be honest, fair and responsible, have a vision, and be able to provide inspiration, and be competent in their field. Educational Leadership Models in Islam, contingency, participation, goal oriented and achievement oriented.